Istanbul 2010 - Dönmez-Colin, Gönül (Kinema: A Journal for Film and Audiovisual Media, 2010)
29th ISTANBUL INTERNATIONAL FILM FESTIVAL 2010 The Istanbul International Film Festival, the largest of its kind in the country, has enriched its repertoire this year with 200 films under twenty-three categories ranging from the prestigious products of 2009 and recent films of 2010 to all time classics. Concentrated largely around the Beyoğlu quarter, where the Turkish national cinema was born, the festival stretched over two weeks, with the second week specially designed for the foreign guests. This year the foreigners had a chance to explore the magnificent city, the Cultural Capital of Europe for 2010, even longer, when the eruption of the Eyjafjallajokul volcano in Iceland paralyzed most European air traffic for several days. The opening film was the melodrama Le concert (The Concert) by Radu Mihaileanu, a France-Italy-Romania and Belgium co-production that explored the issue of identity through classical music. Among the eleven films.